Approach to weak signal extraction and detection via sparse representation - Ya-fei TANG; Yun-yong ZHANG; Zhi-bin GUO (Tongxin xuebao)
The sparsity models and their popular evaluation algorithms were presented.A sparse representation based approach to weak signal extraction and detection was proposed.Furthermore,a fast algorithm was developed to reduce the computational complexity of the proposed method.In addition,both qualitative and quantitative evaluation methods were designed to analyze the proposed approach.A large number of experiments demonstrate the robustness and the adaptivity of the proposed approach.